Mechanical response improvement of crushed rock with cement modification - Siripun, Komsun; Jitsangiam, Peerapong; Nikraz, Hamid (CI-Premier, 2010)
This paper aims to report the mechanical behaviour improvement of crushed rock base (CRB) as a granular road base material subjected to static and cyclic loads from triaxial tests with various stress paths in order to obtain more understanding of road base modified material. As is well known, pavement surface rutting, longitudinal and alligator cracks are normally the main cause of damage in flexible pavements. Currently, existing and natural materials are unable to cope with the premature deterioration. Factors contributing to such damage are the excessive irreversible and reversible deformation of a base layer including the behaviour of a mechanical response of unbound granular materials (UGMs) under traffic load is not well understood. The cement modification was utilized to enhance limited use of raw crushed rock subjected to different stress conditions. Crushed rock was mixed with 2% cement content named hydrated cement treated crushed rock base (HCTCRB) at particular 100% optimum moisture content (OMC) and 100% maximum dry density (MDD) then was kept in various hydration periods to investigate the hydration effect.Subsequently, each hydration of mixture was retreated and re-mixed with specific OMC and MDD of each hydration period and was kept for 28 days for curing. The retreating process is used to avoid micro-crack that usually generate by stabilised procedure. Finally, compacted samples were subjected to static triaxial tests, resilient modulus and permanent deformation in order to simulate the real condition of pavement. The study reports that HCTCRB was enhanced the static and dynamic responses. Moreover, the effects of mechanical responses were investigated and the limit uses of using HCTCRB as a pavement material were determined.